Cultural interfaces and collisions: the influence of western cinema on Zimbabwean youth culture. - Chimanga, Thelma (Midlands State University, 2017)
TV has been considered as powerful on its watchers particularly on their behavioural limit and their social values. The review looked at the impact of western film on Zimbabwean adolescents. The review was tied down on the cultivation theory which takes a glimpse at the impacts of TV on the estimations of its group of onlookers. The second hypothesis which was utilized is cultural imperialism theory which demonstrates that overwhelming western media substance force their social values on underdeveloped nations. Using qualitative research design, the questionnaire as an instrument, 50 students from MSU Zvishavane campus responded .10 students were also interviewed and the researcher made some observations. Results publicised that western cinema prejudiced the dress sense, sexual orientation and beliefs of youths amongst others. As an outcome of watching western television programs youths now imitate foreign ways of living. The researcher settled that normally adolescences have a destructive attitude towards their country and the culture which comes with it. It was recommended that product producers should be more original in the production of local programs, parents should supervise their children on the type of media they watch and also teenage pregnancies should be presented as having dreadful negative effects.